2022
DOI: 10.33222/juara.v7i2.1970
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Leg Length, Leg Flexibility and Leg Speed to the Results of Kedeng Sepaktakraw's Smash Ability

Abstract: Smash kedeng sepaktakraw owned by players is not good, so the smash ball is often not directed and stuck in the net. This study aimed to analyze the contribution of leg length, leg flexibility, and foot speed to the kedeng smash ability of extracurricular male students of SMPN 2 Mandiraja Banjarnegara. This study uses regression and correlational methods or the contribution of four variables. The sample used was 30 male extracurricular takraw students at SMPN 2 Mandiraja. The independent variables in thiSmash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Fundamental motor skills have been considered the primary goal of physical education programs (Febrianto, Sulaiman, & Hidayah, 2022;Kurniawan, Junaidi, & Hidayah, 2022), as evidence shows that the sequence of development is in the behaviour of motor skills with mastery of fundamental motor skills as a prerequisite for the introduction of particular sports and games (Goodway, Ozmun, & Gallahue, 2019). In addition, it is essential for children to learn basic motor skills from an early age, as they are a prerequisite for successful participation in healthrelated physical activities during childhood and even during adulthood (Simpson, Ellison, Carnegie, & Marchant, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Fundamental motor skills have been considered the primary goal of physical education programs (Febrianto, Sulaiman, & Hidayah, 2022;Kurniawan, Junaidi, & Hidayah, 2022), as evidence shows that the sequence of development is in the behaviour of motor skills with mastery of fundamental motor skills as a prerequisite for the introduction of particular sports and games (Goodway, Ozmun, & Gallahue, 2019). In addition, it is essential for children to learn basic motor skills from an early age, as they are a prerequisite for successful participation in healthrelated physical activities during childhood and even during adulthood (Simpson, Ellison, Carnegie, & Marchant, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, a study by Sukadana & Suwardi (2017) investigated crucial factors influencing the accuracy of a sepak takraw athlete's smash, revealing significant insights, though the specific findings remain undisclosed. For example, research by (Febrianto et al, 2022) delves deeper into the interrelationships between physical and technical factors in achieving optimal Smash precision. The research results showed a big relationship between the variable jump height and the ability of athletes to perform the Smash technique accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Futsal games are not only used as a recreational sport, but have become a sport of achievement that is competed in various regional, national and international events (Kharisma &;Mubarok, 2020). The game of futsal is currently loved by many people, especially young people both men and women (Hidayati et al, 1896).…”
Section: Introductionmentioning
confidence: 99%